المصطلح النقدي بين الأصالة والتغريب - عتيق, عمر (Sciences humaines, 2014)
يسعى البحث (المصطلح النقدي بين الأصالة والتغريب ) إلى طرح سؤالين ؛ الأول : هل البحث عن أصل المصطلحِ النقدي : ضرورة علمية أم ترف فكري ؟ فالباحث يستطيع أن يقيس تقدّم الأمة حضارياً، ويحدّد ملامح ثقافتها عقيدة وفكراً، بإحصاء مصطلحاتها اللغوية ومعرفة مدلولاتها، بل يستطيع أن يتأكد من وحدة الأمة الفكرية والسياسية من وحدة مصطلحاتها اللغوية. والسؤال الثاني : ما أسباب اغتراب المصطلح وتعدده واضطرابه ؟ وهي أسباب تتلخص بالإعجاب بالآخر واختلاف السياق الثقافي وغياب المنهجية وتقصير المجامع اللغوية  والترادف اللغوي.   Résumé : This research (the critical term between authenticity and alienation) tries to ask two questions, the first is, whether the search for the origin of the critical term is an academic necessity or an auxiliary thinking. The researcher can measure the progress of the civilized nation, and to identify the cultural features of thought and doctrine, by counting its language terminology and the knowledge of its indication, he can also be sure of the unity of the nation intellectually and politically through the unity of its terminology. The second question is what are the reasons behind the alienation, plurality and disturbance of the term? These reasons can be summed up by the admiration of the other, and the difference of the cultural context, the absence of the methodology failure of the language academies and the synonym of the language.